Rancang Bangun Sistem Informasi Rekapitulasi Kehadiran Siswa Untuk Guru Pengampu Mata Pelajaran Madrasah Aliyah Ma’arif Pacitan Menggunakan Php Dan Mysql - Syahbana, Ali (Seruni - Seminar Riset Unggulan Nasional Inoformatika dan Komputer, 2012)
ABSTRACT: MA Ma'arif Pacitan is one private school in Pacitan, which addressed on Jl. Cokroaminoto HOS. 9B Pacitan. List of school attendance is one of the administration are very important for smooth teaching and learning activities. With the administration of student attendance will help teachers pengampu subjects to determine the level of attendance of each learner. The concept of information system design refers to the administration of the presence of students who come to every meeting of teachers pengampu subjects. The system is created using PHP script as the server side HTML embedded scripting, as a web server apache and mysql for database processing. All that is included in onesoftware package XAMPP. The design of these systems have components such as class data, student data, attendance data types, data gathering teaching, data gathering failed teaching, student attendance data. This system makes the solution more quickly for teachers pengampu subjects to give the action on the students. Keyword : Student Attendance, Pengampu Teachers, PHP, Apache, Mysql Abstraksi : Madrasah Aliyah Ma’arif Pacitan merupakan salah satu sekolah swasta di Pacitan, yang beralamatkan di Jl. HOS Cokroaminoto No. 9B Pacitan. Daftar kehadiran siswa adalah salah satu administrasi yang sangat penting bagi kelancaran kegiatan belajar mengajar. Dengan administrasi kehadiran siswa akan membantu guru pengampu mata pelajaran untuk mengetahui tingkat kehadiran setiap anak didik. Konsep perancangan sistem informasi ini mengacu pada kegiatan administrasi kehadiran anak didik yang terjadi di setiap pertemuan guru pengampu mata pelajaran. Sistem ini dibuat menggunakan script PHP sebagai server side HTML embedded scripting, apache sebagai web server dan mysql untuk pengolahan databasenya. Semua itu sudah tercakup pada satu paket perangkat lunak XAMPP. Perancangan sistem ini memiliki komponen seperti data kelas, data siswa, data jenis absensi, data pertemuan mengajar, data pertemuan mengajar gagal, data kehadiran siswa. Sistem ini membuat solusi lebih cepat bagi guru pengampu mata pelajaran untuk memberi tindakan pada anak didik. Kata kunci: kehadiran siswa, guru pengampu, PHP, Apache, Mysql